2021
DOI: 10.3390/pr9112016
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Source Contributions and Health Risk Assessment of Fine Particle-Bound Polycyclic Aromatic Hydrocarbons (PAHs) during Spring and Late Summer in the Baoshan Area, Shanghai

Abstract: The main objective of this study was to examine the chemical characteristics, possible sources, and health risks of fine particle-bound Polycyclic Aromatic Hydrocarbons (PAHs) in the Baoshan area of Shanghai. Here, ambient particles with five-size ranges were collected during the spring and late summer of 2017. The PAHs were determined by the Gas Chromatography-Mass Spectrometry (GC-MS). Our results showed that the average mass concentration of 13 species of PAHs in spring and in late summer was 4.83 (1.88~12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In contrast, low-molecular-weight PAHs were highest in summer (49%), reflecting the influence of enhanced photochemical processing. It is usually considered that low-molecular-weight PAHs are formed during low-temperature processes such as biomass burning [ 38 ]. This finding can be partly attributed to the impact of biomass burning within the Polish study domain, which was confirmed by the relatively high contribution of low-molecular-weight PAHs to total PAHs ( Figure 2 ) and their seasonality ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, low-molecular-weight PAHs were highest in summer (49%), reflecting the influence of enhanced photochemical processing. It is usually considered that low-molecular-weight PAHs are formed during low-temperature processes such as biomass burning [ 38 ]. This finding can be partly attributed to the impact of biomass burning within the Polish study domain, which was confirmed by the relatively high contribution of low-molecular-weight PAHs to total PAHs ( Figure 2 ) and their seasonality ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the retention period of the target ion peak (within 0.05 min of the calibration standard's retention), each unique PAH was identified. Each sample was selected three times, and Microsoft Excel 2022 handled the statistical processing [49]. The analyzed PAHs were as follows: Acenaphthene (Acy), Anthracene (Ace), Benz…”
Section: Analysis Of Pahsmentioning
confidence: 99%
“…where TEQ s -total toxic equivalent content, µg/kg; C i -the content of monomeric PAHs, µg/m 3 ; TEF i -toxicity of monomeric PAHs equivalence factor; TEF is taken as shown in Table 2 [53,54]. PAHs pose a carcinogenic risk to humans through three main routes: ingestion pathways (ILCRing), inhalation pathways (ILCRinh), and dermal-contact pathways (ILCRder).…”
Section: Health Risks Assessmentmentioning
confidence: 99%